2010
DOI: 10.1097/brs.0b013e3181c6d9ae
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Comparisons Between the Pedicle and the Pedicle Rib Unit in the Immature Chinese Thoracic Spine

Abstract: Compared with the dimensions of the immature pedicle, the significantly larger size of the corresponding pedicle rib unit provides a more ample space, which accommodates screws with larger diameters. Extrapedicular vertebral body fixation was anatomically feasible for the immature spine. The new procedure should be cautiously applied to avoid potential implant failures or a new deformity because of the growth of the immature spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…We measured the following parameters using the Star PACS System, which was proven to achieve accurate measurements in previous studies [ 8 , 18 ]:…”
Section: Methodsmentioning
confidence: 99%
“…We measured the following parameters using the Star PACS System, which was proven to achieve accurate measurements in previous studies [ 8 , 18 ]:…”
Section: Methodsmentioning
confidence: 99%
“…However, pedicle violation resulted from malpositioned screw leading to potential harm to nearby vital structures, which prompted surgeons to search for the perfect strategy. Though alternative methods (e.g., transarticular screw [2], lateral mass [3], extrapedicular screw fixation [4,5]) were developed for better surgical outcome, surgeons were more prone to improve the pedicle screw insertion accuracy by trying various supporting methods (e.g., intraoperative monitoring [6,7], anatomical markers [13,24,26,47]). Nevertheless, none of the conventional methods was considered as the perfect intraoperative assisting method.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Liljenqvist et al [ 16 ] measured 26 patients with right-side thoracic curves using MRI and found significantly narrower pedicles on the concave side at the apex of the curve (range of 2.3–3.2 mm compared with convex side 3.9–4.4 mm), whereas the width of pedicle rib unit was wider when compared with the convex side (ranged from 11 mm in the cephalad aspect to 14 mm in the caudad aspect of the thoracic spine). Tian et al [ 17 ] also investigated the dimensions of the pedicle rib unit for normal children, reporting a significantly larger size of the corresponding pedicle rib unit provided a more ample space. Furthermore, the minimum value of maximal screw length of CBT screws insertion via pedicle rib unit was 6.27 mm (Table 3 ), which indicated that 5.5 mm CBT screws can be inserted correctly via the pedicle rib unit in all patients (Fig.…”
Section: Discussionmentioning
confidence: 99%